2013
DOI: 10.3390/ijms14024106
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative Activities and Apoptosis Induction by Triterpenes Derived from Eriobotrya japonica in Human Leukemia Cell Lines

Abstract: Eriobotrya japonica leaf is a traditional herbal medicine that contains numerous triterpenes, which have various pharmacological properties. In this study, we investigated the anti-proliferative activity of four triterpenes derived from E. japonica, including corosolic acid (CA), ursolic acid (UA), maslinic acid (MA) and oleanolic acid (OA), in human leukemia cell lines. CA showed the strongest anti-proliferative activity in all of the leukemia cell lines tested, but not in normal human skin fibroblast cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…Previously, the cytotoxicity of 28-hydroxy-3-friedelanone against A549-human lung cancer cell line, LLC-mouse Lewis lung carcinoma, HL60-human promyelocytic cell line, and MCF7-human breast cancer cell line were demonstrated. Hence, some triterpenes could strongly induce apoptosis by attending the mitochondrial membrane potential and regulating the expression of Bcl-2 different compasses [14, 20]. The IC 50 ( μ g/mL) of 7-methoxy-coumarin 3 on HL60 and K562 human chronic leukemia cells was also demonstrated with the values of 28.9 and 19.3  μ g/mL, respectively [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the cytotoxicity of 28-hydroxy-3-friedelanone against A549-human lung cancer cell line, LLC-mouse Lewis lung carcinoma, HL60-human promyelocytic cell line, and MCF7-human breast cancer cell line were demonstrated. Hence, some triterpenes could strongly induce apoptosis by attending the mitochondrial membrane potential and regulating the expression of Bcl-2 different compasses [14, 20]. The IC 50 ( μ g/mL) of 7-methoxy-coumarin 3 on HL60 and K562 human chronic leukemia cells was also demonstrated with the values of 28.9 and 19.3  μ g/mL, respectively [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Eriobotrya japonica leaf is included in the Chinese Pharmacopoeia [1] and widely used as a medicinal material in traditional treatment of a variety of chronic diseases in China and other East Asian countries [2]. Phytochemical investigations showed that its main components are essential oil, triterpenes, sesquiterpenes, flavonoids, tannins, and megastigmane glycosides [3].…”
Section: Introductionmentioning
confidence: 99%
“…PCR was carried out on a 7900HT Fast Real-Time PCR System (Applied Biosystems/Life Technologies, Carlsbad, CA, USA). The reaction mixture containing 10 μL of 2 × Fast SYBR Green Master Mix, 0.4 pmol sense and antisense primers, and 2 μL diluted cDNA (17) was loaded onto a 386-well plate; amplification was carried out under the following conditions: 95°C for 20 s, followed by 40 cycles of 95°C for 1 s and 60°C for 20 s. The following sense and antisense primers were used: human GOAT, 5′-ACAGCTCGA Triterpenes are phytochemicals consisting of six isoprene units that have anti-oxidant, anti-inflammatory, and anti-proliferative effects (2,22,24). Certain triterpenes such as asiatic acid, betulinic acid, corosolic acid, glycyrrhetinic acid, oleanolic acid, and ursolic acid have shown anti-obesity effects in mice fed a high-fat-diet (4,5,18,19,23,25).…”
Section: Quantitative Reverse Transcriptase (Qrt)-pcr Analysismentioning
confidence: 99%